Risk factors for the development of necrotizing enterocolitis in neonatal hemolytic disease: a mini review - Yu, Haiyue; Guo, Wanxu; Wang, Yuan; Zhang, Yunfeng (Frontiers in Pediatrics, 2025)
Hemolytic disease of the newborn (HDN) is a common disease of neonates, and necrotizing enterocolitis (NEC) is a serious gastrointestinal disorder and both occur in the neonatal period that can significantly increase the risk of death in children. Cases of NEC associated with HDN are increasing. The purpose of this paper is to collect and present relevant research data to understand the risk factors associated with necrotizing enterocolitis in neonatal hemolytic disease, and to provide reasonable guidance and reference for clinical work.